THE ANALYSIS OF HORMONAL STATUS IN PERIOD OF SOMATO-SEXUAL DEVELOPMENT AMONG TEENAGERS - Гудзевич, Л.С.; Куц, Б.О. (World of Medicine and Biology, 2016)
The results of the research of hormonal balance characteristics of teenagers in period of somato-sexual development showed that hormonal diagnostic gives the opportunity to find the ornery indications and causes of unfavorable effects caused by medical-social factors. In the article showed also the influence on the genesis of problems with health own hormonal disfunctions, relations between the genesis of hormonal infraction in different geographic regions of Ukraine and the perspective of normativ hormon level modeling. The difference between sexes and non-equality of hormon level in boys and girls organisms in puberty were found. The universally recognised fact is the influence on changes of cortisol, prolactin, sexul steroides, tireotropin levels among patients with fat mass, poor mass, alcoholism in some regions of Ukraine and other concomitant diseases in period of teenage making. It is worth to consider the rates of individual well-being and already today to hammer the improvement of life quality for teenagers.
Keywords: teenagers; hormonal status; hormons; somato-sexual development; factors